Future is a Carefully Neutralized Present - Andrey Vaganov (Foresight and STI Governance)
The article finalizes the results of the young scientists’ essay competition “Create the future” which was organized at the end of 2008 by the Institute for Statistical Studies and Economics of Knowledge and the Foresight Сentre of the Higher School of Economics. The author has analyzed received papers and identified several similar trends which authors addressed in their forecasts with regard to nanotechnology applications in various areas of our everyday life. As a result, he drew up a rating of young scientists’ technological expectations from the future. Leading positions of the rating (from the point of view of number of references) belong to subjects related to health, aging, practical immortality, nanomaterials and electric vehicles, and household use of nanotechnologies. The jury had to choose three best essays out of fifty. The winners dedicated their papers to “one day of a Russian citizen in 2025”. The essay which took the first place has been published in the current issue of the journal.